Chitons' apparent camouflage does not reduce predation by green crabs Carcinus maenas. Issue 2 (7th February 2016) - Mendonça, Vanessa; Vinagre, Catarina; Boaventura, Diana; Cabral, Henrique; Silva, Ana C. F.
ABSTRACT: Chitons are very common molluscs on European rocky shores. They are common prey of fish and crabs and often display several colour morphs within a given habitat. Predation is one of the potential mechanisms accounting for chiton colour polymorphism. The colour variation is considered to provide a camouflage protection through a match with the substratum surface typology. However, the effectiveness of chiton polymorphism as a predation defence requires further investigation. Previously we found a relationship between chiton colour morphs and substrate characteristics, with chitons most commonly found on substrates that were of similar colour to their shells. Here, we examined whether each morph displayed an active choice for matching the substratum. Next, we assessed if the predation success of the intertidal common crab Carcinus maenas varied significantly with the absence/presence of an apparent camouflage effect created between the chiton colour morph and the substratum type. The present study indicates that chiton colour morphs probably actively choose substratum types where they blend in. Carcinus maenas was able to prey on all Lepidochitona cinereus colour morphs, regardless of the substrate camouflage effect. Surprisingly, the predation frequency was higher on camouflaged chitons than on contrasting chitons. It was concluded that chiton camouflage is probably not a defence mechanism against predation by the crab C. maenas, and that chiton colour polymorphism is probably promoted by other, more visual predators.